2016
DOI: 10.1104/pp.16.00110
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of autophagy by sulfide in Arabidopsis thaliana is independent of reactive oxygen species

Abstract: Accumulating experimental evidence in mammalian, and recently plant, systems has led to a change in our understanding of the role played by hydrogen sulfide in life processes. In plants, hydrogen sulfide mitigates stress and regulates important plant processes such as photosynthesis, stomatal movement, and autophagy, although the underlying mechanism is not well known. In this study, we provide new experimental evidence that, together with our previous findings, demonstrates the role of hydrogen sulfide in reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 87 publications
(109 reference statements)
5
56
0
Order By: Relevance
“…This might lead to a mechanism in which NO could also directly inactivate the autophagic process. Moreover, NO was shown to induce the expression of genes encoding hydrogen sulfide (H 2 S)-synthesizing enzymes in tomato plants [131] resulting in higher levels of H 2 S, which inhibits autophagy by an unknown mechanism [132]. This effect of NO would be less relevant when SnRK1 is more active because SnRK1 was shown to phosphorylate nitrate reductase (NR), inactivating its activity and thus reducing NO production [133].…”
Section: Ros Levelsmentioning
confidence: 99%
“…This might lead to a mechanism in which NO could also directly inactivate the autophagic process. Moreover, NO was shown to induce the expression of genes encoding hydrogen sulfide (H 2 S)-synthesizing enzymes in tomato plants [131] resulting in higher levels of H 2 S, which inhibits autophagy by an unknown mechanism [132]. This effect of NO would be less relevant when SnRK1 is more active because SnRK1 was shown to phosphorylate nitrate reductase (NR), inactivating its activity and thus reducing NO production [133].…”
Section: Ros Levelsmentioning
confidence: 99%
“…H 2 S has also been reported to play a very important role in autophagy (Laureano‐Marín et al ). In Arabidopsis, sulfide inhibits autophagy in the roots under nutrient deprivation by preventing the accumulation of ATG8 (AUTOPHAGY‐RELATED UBIQUITIN‐LIKE PROTEIN).…”
Section: Role Of No and H2s As Signaling Moleculesmentioning
confidence: 99%
“…Furthermore, addition of exogenous sulfide to a des1 mutant or genetic complementation of DES1 gene prevented the accumulation and lipidation of ATG8 proteins (Álvarez et al, 2012). Recently, it was demonstrated that the negative regulation of autophagy by sulfide is independent of reactive oxygen species, and sulfide therefore probably regulates autophagy by an alternative pathway (Laureano-Marín et al, 2016).…”
Section: Other Possible Regulatorsmentioning
confidence: 99%